Projecting global shifts in the invasive potential of Bidens pilosa L. under climate change using species distribution models - Fan, Linran; Mi, Chunxiao; Li, Jialu; Zhang, Yanjun; Zhang, Haifang; Zhang, Guilong; Wang, Hui (Frontiers in Plant Science, 2025)
Invasive species pose significant threats to ecosystems by reducing biodiversity, introducing new diseases, and competing with native species for resources. Bidens pilosa L., a globally invasive weed originating in tropical America, severely impacts agricultural productivity by infesting 31 economically vital crops across over 40 countries. This study examined the global distribution of Bidens pilosa L., under current and future climate scenarios. Using species distribution models and occurrence data, we identified key factors influencing its spread, including temperature, precipitation, and human influence. Our findings suggest a likely decline of suitable habitats in tropical regions and an expansion into temperate regions, with climate suitability decreasing under higher temperatures. Additionally, historical reconstructions emphasize that the rapid spread of the species was facilitated by maritime trade routes. Management strategies are proposed that emphasize the need for enhanced control measures in high-risk areas and conservation efforts in its native range in tropical America. Overall, this research contributes to understanding the dynamics of B. pilosa distribution and informs proactive management strategies to mitigate its ecological and economic impacts.